And the organizational commitment of Teachers - Salvador Cornelio, Elena M. (2018)
This work gathers objective data that allow us to analyze the correlation between the leadership of the Directors and the organizational commitment of teachers. The objective of the work is to determine the significant relationship of managerial leadership and teacher organizational commitment in Educational Network N ° 22-Unit of Management 01. Basic methodology of a quantitative nature and used a non-experimental, cross-sectional design, descriptive correlational level. Population is finite and the sampling was probabilistic. We use two validated and reliable instruments. Correlation results rho Spearman =, 676 and a p value = 0.000 lower than the level α = 0.05. Conclusion There is a moderate significant relationship between the Leadership Leadership and Organizational Commitment in the teachers of the Educational Network N ° 22-UGEL 01.